Divergent cardio-ventilatory and locomotor effects of centrally and peripherally administered urotensin II and urotensin II-related peptides in trout - Vanegas, Gilmer; Leprince, Jérôme; Lancien, Frédéric; Mimassi, Nagi; Vaudry, Hubert; Le Mével, Jean-Claude (Frontiers in Neuroscience, 2015)
The urotensin II (UII) gene family consists of four paralogous genes called UII, UII-related peptide (URP), URP1 and URP2. UII and URP peptides exhibit the same cyclic hexapeptide core sequence (CFWKYC) while the N- and C-terminal regions are variable. UII, URP1, and URP2 mRNAs are differentially expressed within the central nervous system of teleost fishes, suggesting that they may exert distinct functions. Although the cardiovascular, ventilatory and locomotor effects of UII have been described in teleosts, much less is known regarding the physiological actions of URPs. The goal of the present study was to compare the central and peripheral actions of picomolar doses (5–500 pmol) of trout UII, URP1, and URP2 on cardio-ventilatory variables and locomotor activity in the unanesthetized trout. Compared to vehicle, intracerebroventricular injection of UII, URP1 and URP2 evoked a gradual increase in total ventilation (VTOT) reaching statistical significance for doses of 50 and 500 pmol of UII and URP1 but for only 500 pmol of URP2. In addition, UII, URP1 and URP2 provoked an elevation of dorsal aortic blood pressure (PDA) accompanied with tachycardia. All peptides caused an increase in locomotor activity (ACT), at a threshold dose of 5 pmol for UII and URP1, and 50 pmol for URP2. After intra-arterial (IA) injection, and in contrast to their central effects, only the highest dose of UII and URP1 significantly elevated VTOT and ACT. UII produced a dose-dependent hypertensive effect with concomitant bradycardia while URP1 increased PDA and heart rate after injection of only the highest dose of peptide. URP2 did not evoke any cardio-ventilatory or locomotor effect after IA injection. Collectively, these findings support the hypothesis that endogenous UII, URP1 and URP2 in the trout brain may act as neurotransmitters and/or neuromodulators acting synergistically or differentially to control the cardio-respiratory and locomotor systems. In the periphery, the only physiological actions of these peptides might be those related to the well-known cardiovascular regulatory actions of UII. It remains to determine whether the observed divergent physiological effects of UII and URPs are due to differential interaction with the UT receptor or binding to distinct UT subtypes.